Screening for Body Dysmorphic Disorder among Patients Seeking Dermatological and Cosmetic Care: A Cross-sectional Study - Valérie Peeters; Sherief R. Janmohamed; Samira Baharlou; Jan Gutermuth; Ria Willemsen (Medical Journals Sweden, 2021)
Abstract is missing (Short communication)